Neuro-Fuzzy Routing with Clusters in Wireless Sensor Network - Lissy, D; Behin Sam, S (International Journal of Computer Sciences and Engineering, 2018)
Wireless Sensor Networks (WSN) are used in a extensively large number of applications. Based on the advanced development of sensors nodes, routing of data becomes an interesting concept in WSN. Many routing protocols were designed by researchers all over the world concerning about battery power, sensing data, networking lifetime and transmitting data etc. This paper concentrates on routing the data in an intelligent manner than the existing routing protocols. Aggregating the data with the help of clusters from the nearby nodes and the cluster heads are responsible to send the collected data to one or more Sink Node(SN) that request for data. This paper ponders on clustering with neurons in the cluster heads and thereby gathers the needed and correctly sensed information very faster based on fuzzy inference system. Neuron in the form of cluster heads gathers and remembers the data. With the help of NS2 simulator this algorithm is very clear that it surpasses the other routing protocols in an abundant number of ways.